Turkey and the Strategy of Britain's Security in the Middle East (1954-1955) - Dwelee, Alaa Hamza; Musa, Alaa Jaber (Al-Adab Journal, 2022)
The issue of securing Britain's security in the Middle East after WWII had a great importance in British Politics. Britain was exhausted from the war despite its victory, therefore it had to look for an alternative to help secure its defenses in the Middle East and found Turkey as their best choice. Turkey was eager to play the guardian role of British interest in the region to secure its political and economic interests, gain as much as they can of military assistance from Britain and allies and to protect themselves from the Soviet danger. Due to the importance of the issue, the study focuses on Turkey’s role in securing British strategy in the Middle East for the period from the signing the Turkish-Pakistani agreement on April 4th, 1954 to the singing of the Turkish-British agreement on April 4th, 1955, as well as the impact of the British-Turkish policy in the Middle East and their alliance.The Study discussed the importance of Turkey’s role in British security in the Middle East and Britain's stand of the Turkish-Pakistani agreement. It also discussed (Baghdad Pact) the cooperation between Iraq and Turkey, Turkey’s role in drafting the pact, Britain's gains from it and its role in rebuilding Britain's defenses according to the Iraqi-British agreement on April 4th, 1955.The study has several conclusions; Britain had achieved what it is called Defense by Proxy to secure its strategy in the Middle East and protect its political and economical interests by using Turkey as a tool. Additionally, Britain succeeded in directing Turkey's policy with what suits its Defense Policy in the Middle East. Turkey also fulfilled its goal of proving its trustworthiness to great powers such as Britain and the United States, as well as securing the northern front from the Soviet Union and securing the flow of military assistant.